The Detection of Mixed Infection with Canine Parvovirus, Canine Distemper Virus, and Rotavirus in Giant Pandas by Multiplex PCR - Ai Liu; Wenyue Qiao; Rui Ma; Qigui Yan; Shan Zhao; Yifei Lang (Veterinary Sciences)
The well-being and subsistence of giant pandas, an endangered species with a limited distribution, are currently threatened by a number of viruses, including canine parvovirus (CPV-2), canine distemper virus (CDV), and giant panda rotavirus (GPRV). To allow for timely intervention upon viral infection, it is necessary to execute rapid and accurate diagnosis of potential mixed viral infections. In the present study, we developed and validated a multiplex PCR (mPCR) approach for the detection of CPV-2, CDV, and GPRV infections. The results indicate that the method could selectively amplify the three viruses with high sensitivity and specificity, which are necessary attributes in clinical settings. Utilizing the established method, (sub)clinical giant panda samples were examined, and CPV-2, CDV, and GPRV were found in 19.72% (43 out of 218), 7.34% (16 out of 218), and 6.42% (14 out of 218) of the samples, respectively. Noticeably, mixed infections of two or three viruses were common, and this was generally observed in CDV- or GPRV-positive samples. Meanwhile, mPCR results were further validated with sequencing and the phylogenetic analysis of full-length sequences of viral genes. Taken together, our study provides an approachable assay which enables the quick detection of the three viruses mentioned above, which will benefit clinical diagnosis and laboratory epidemiological-based investigations of the giant panda population.